Inferior alveolar nerve paraesthesia after overfilling into the mandibular canal, confirmed by cone-beam computed tomography: a case report - Souza Júnior, Claudemir de; Machado, Ricardo; Batts, Renee Ashley; Garcia, Lucas da Fonseca Roberti (Brazilian Dental Science, 2021)
The filling material should be restricted to the root canal, and not extend to the periradicular tissues. Overextension occurs when there is an overflow of gutta-percha and sealer, whereas overfilling refers to the overflow only of sealer beyond the apical foramen. Both may cause several negative clinical consequences. Nevertheless, an accurate diagnosis of where they occurred cannot always be performed by conventional radiographic examination, because of the two-dimensional aspect of the image. This paper describes a clinical case of labiomandibular paraesthesia after overfilling into the mandibular canal (MC), as diagnosed by cone-beam computed tomography (CBCT), later used to perform the treatment planning. A 34-year-old Caucasian female patient sought a private dental clinic complaining of pain in the right mandibular posterior region. After taking the anamnesis and performing clinical and radiographic exams, the patient was diagnosed with pulp necrosis in the second right mandibular molar, and underwent root canal treatment. The final radiography showed overextension or overfilling, probably into the MC. About 2 hours after the procedure, the patient reported paraesthesia of her lower right lip and chin. A CBCT confirmed a small overfilling into the MC. For this reason, vitamin B12 was prescribed as the first treatment option. After 7 days, the patient reported a significant decrease in paraesthesia, and was completely normal after 15 days. This case report shows that CBCT is an effective radiographic diagnostic tool that can be used as an alternative in clinical cases of labiomandibular paraesthesia caused by overextension or overfilling. Keywords Endodontic treatment; Overfilling; Paraesthesia; Conebeam computed tomography.